Use of Coliphages as an indicators of enteroviruses and faecal pollution in Water (Baghdad Science Journal, 2011)
In spite of increasing clinical cases which caused by enteroviruses transferred by water and no documents about entericviruses in the Iraqi water standards. The use of coliphages as an indicator of enteroviruses and fecal pollution were suggested two procedures were applied . The first is Two-Step Enrichment Method and the second is Single Agar Layer Method. Both methods gives good results in Identification of coliphages through testing fifty different water samples (Tap water, Surface water and Bottled water) the study shows the presence of coliphages in fourteen samples.